An Assessment of Revenue Mobilization in Nigeria Local Government: Problems and Prospects. - Dada, Raphael Adekola; Adebayo, Isaac Adesodun; Adeduro, Ogunmakin Adesola (Archives of Business Research, 2017)
This study assessed the prospects and problems of revenue mobilization in Nigerian Local Governments. It specifically determined the significant impact of development on internally generated revenue of local government in Nigeria; assessed the impact of financial misappropriations on internally generated revenue in the local government in Nigeria. The study employed the use of closed ended and likert scale ranked, well-structured questionnaire as the source of data collection. The responses of the questionnaire were coded and later analyzed with the use of inferential (multiple regression) statistics. The study revealed that development has significant impact of 21.9% (t= 3.575 and p< 0.05) on internally generated revenue of local government in Nigeria, while financial misappropriation has significant impact of 26.5% (t= 4.668 and p<0.05) on internally generated revenue of local government in Nigeria. The study concluded that the level of development (human and infrastructural) and the rate of financial misappropriation are determinants to the revenue base of Nigerian local governments. It is recommended that Nigerian local government authorities should ensure both human and infrastructural development in their respective constituencies as this is influential on the level of revenue derivation. In addition, local government authorities should ensure a carrot and stick approach whereby members of staff are rewarded on performance and strictly punished for perpetrating financial misappropriations in other to curb the menace of the anathema on the fabric of the society.